Functional Natural-Based Polymers - Mignon, Arn (2022)
Natural polymers are already used for a variety of biomedical applications, including drug delivery, wound healing, tissue engineering, biosensors, etc. However, they have also found other applications, for example, in the food industry, the pharmaceutical industry, as firefighting materials, water purification, etc. Different polysaccharide and protein-based systems have been developed. They each have their properties that render them useful for certain applications such as the water solubility of alginate, the thermo-sensitivity of chitosan, the abundance of cellulose and starch, or the cell adhesion and proliferation of gelatin and collagen. This Special Issue will explore the design, synthesis, processing, characterization, and applications of new functional natural-based polymers.